A study on IL-35 gene polymorphism and mRNA expression in patients with rheumatic heart disease - Reddy, Penagaluru Pardhanandana; Sultana, Shehnaz; Yerra, Shiva Kumar; Penagaluru, Pranay Krishna (International Journal Of Community Medicine And Public Health, 2025)
Background: Rheumatic heart disease (RHD) is a chronic heart valve condition affecting around 40 million people globally. Inflammatory cytokines, acting as messengers, play a role in immune responses in various rheumatic diseases. Anti-inflammatory cytokines, produced by B cells and T cells, act as regulatory molecules controlling pro-inflammatory responses. Among these, Interleukin-35 (IL-35) stands out as a promising target for potential therapies in autoimmune and inflammatory diseases. Genetic variations and expression levels of IL-35 genes might have an impact on individuals with RHD. Methods: This study is aimed to explore the connection between gene polymorphisms and mRNA expression levels in both RHD patients and control subjects. The investigation involved 135 RHD patients and 140 control subjects, utilizing RT-PCR as the methodology. Results: The findings revealed a significant association between RHD and heterozygous variant (GC) (OR-1.77, 95% CI 0.3-3.04) and minor allele (C) (OR-0.60, 95% CI 0.39-0.92) of the EBi3 (IL-35) gene. In addition, increased mRNA expressions were observed, with a mean of 2.23±1.14 for EBi3 and 2.50±1.53 for IL-12A, indicating a noteworthy association with RHD patients compared to the control subjects. Conclusions: The current study propose that gene polymorphisms could impact IL-35 expression levels in RHD patients. However, further analysis involving a larger number of cases is needed to draw conclusive results.